Annotated checklist of the ground beetles (Coleoptera: Carabidae) of Jordan. Issue 3 (2nd October 2017) - Nasir, Wafa' Mohammed; Katbeh-Bader, Ahmad
Abstract: Carabid beetles were collected by hand picking, pitfall traps and light traps from March 2015 to May 2016 from different habitats within Jordan. A total of 1865 specimens were collected representing 55 species; 27 of them are recorded for the first time from Jordan. A checklist of 136 species, arranged in 16 subfamilies, 28 tribes, and 69 genera, was compiled as a result of recent collecting and bibliographical sources. The valid name, current and previous collecting sites and dates, available biological or ecological data, and coloured photographs were provided for 60 species examined. Male genitalia for 30 species were dissected and photographed.